Low Expression of A3C and PLP2 Indicating a Favorable Prognosis in Human Gliomas: A3C and PLP2 in gliomas - Jin, Jong-Shiaw; Tsai, Yu-Ling; Chang, Yu-Chan; Tsai, Wen-Chiuan (Cellular and Molecular Biology, 2023)
The roles of apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like 3C (A3C) in various human malignancies are not consistent. A3C expression is correlated with early-stage breast cancer and is presented as a good prognostic factor; however, it induces fewer therapeutic effects of cytotoxic drugs in low-grade gliomas. To explore the impact of A3C on gliomas, a statistical analysis of several public databases was conducted. The results showed that enhanced A3C expression was associated with advanced tumor grades and poor expression of prognostic factors. Similarly, our in vitro study revealed that glioblastoma (GBM) cell lines had higher A3C mRNA and protein expression than that of normal brain tissue cDNA and lysates. We first performed an immunohistochemical stain (IHC) to prove that gliomas with high A3C expression presented the wild type-Isocitrate dehydrogenase 1 (IDH1), and they had an unfavorable prognosis in human glioma tissues. In addition, the oncological factors associated with A3C expression suggested that DNA repair pathways are important mechanisms for inducing tumorigenesis and chemoresistance in gliomas. Moreover, a significant correlation was observed between A3C expression and proteolipid protein 2 (PLP2). Reactive oxygen species (ROS) -activated PLP2 prevents DNA damage-induced cell apoptosis. Compared to high immunostaining scores for A3C and/or PLP2 expression, combined low immunostaining scores for A3C and PLP2 correlated with improved survival in gliomas; however, the detailed mechanism is to be elucidated. In conclusion, our results not only confirmed A3C played an important role in glioma development, but the A3C IHC test could successfully predict the therapeutic effects and disease prognosis.